School counselor leadership: A theoretical and empirical review - Uman Suherman; Yusi Riksa Yustiana; Fajriani Fajriani; Yulizar Yulizar (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
Entering the 21st century, the leadership role of teachers is in the spotlight in primary to secondary education. Similarly, the leadership of school counselors began to be voiced. Changes in the orientation of guidance and counseling resulted in a shift in the role of the school counselor as one of the implementers in guidance and counseling management. School counselors exercise a leadership role in developing and organizing guidance and counseling programs. This study aims to describe and how the leadership of school counselors theoretically and empirically. The analysis method uses a literature review with four stages: identification, screening, suitability, and inclusion. The primary data sources are obtained from academic reference books and previous research on teacher leadership, guidance and counseling over the past five years that have been published in reputable journals in the Scopus database. The results showed that school counselor leadership in the last five years carried several themes, such as testing the effectiveness of leadership training interventions, the relationship of leadership with personality attributes, the design of leadership training frameworks, the relationship of counseling leadership with professional counselor identity, and school counselor leadership in the context of ethnicity. The results of this study are expected to provide a broader picture of future research opportunities on the topic of school counselor leadership.